Pengaruh Tingkat Pendidikan dan Pendapatan terhadap Minat Menabung - Dian Apriani; Akhmad Faozan (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
Saving has a very important role for the future because saving is one way to manage finances. Saving means setting aside the money we have to save. Saving is also part of financial planning to deal with future needs. This study aims to measure the effect of education level and income on the interest in saving in the people of Pondoknangka Barat Hamlet, Beluk Village, Belik District, Pemalang Regency. Sampling using accidental sampling with a total of 100 respondents. The data obtained was then processed using the SPSS program using multiple linear regression analysis techniques. The results of the study show that there is a significant influence between education level and income simultaneously on the intention to save.